2023
DOI: 10.1055/s-0043-1760726
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Posttraumatic Tension Pneumocephalus: Case Report and Review of Literature

Abstract: Delayed tension pneumocephalus is a rare entity. Twelve cases of posttraumatic delayed tension pneumocephalus have been reported. This study is a case report of a patient presenting with delayed posttraumatic tension pneumocephalus, and highlights the nuances of management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
(6 reference statements)
0
0
0
Order By: Relevance
“…PN is a neurological emergency characterized by the accumulation of compressed air within the cranial cavity, often associated with accidental decompression, surgical trauma, and impacts involving the face and skull. [18,19] PN is commonly associated with various events such as post-craniotomy or surgical interventions, barotrauma, ear infections, exposure to nitrous oxide or induced nitrogen anesthesia, and diagnostic procedures (e.g., lumbar puncture). [20,21] While the location of PN may vary, it typically manifests with the presence of air in the apical space and encompasses intraventricular, intraparenchymal, subarachnoid, subdural, and epidural areas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PN is a neurological emergency characterized by the accumulation of compressed air within the cranial cavity, often associated with accidental decompression, surgical trauma, and impacts involving the face and skull. [18,19] PN is commonly associated with various events such as post-craniotomy or surgical interventions, barotrauma, ear infections, exposure to nitrous oxide or induced nitrogen anesthesia, and diagnostic procedures (e.g., lumbar puncture). [20,21] While the location of PN may vary, it typically manifests with the presence of air in the apical space and encompasses intraventricular, intraparenchymal, subarachnoid, subdural, and epidural areas.…”
Section: Discussionmentioning
confidence: 99%
“…Despite significant advances in understanding the pathophysiology of PN, the documentation remains limited, with only six confirmed cases of PN and only four cases of TPN properly documented regarding patients with NPC. [19][20][21] Several mechanisms have been identified to explain the occurrence of TPN, with barotrauma being one of the most studied. In this regard, Kankane et al (2016) reported the case of a 50-year-old man who developed TPN due to high air pressure (hyperbaric) following epidural steroid injections for the treatment of cervical radiculopathy.…”
Section: Discussionmentioning
confidence: 99%